Chemistry of muconaldehydes of possible relevance to the toxicology of benzene. - Bleasdale, C (1996)
(Z,Z)-Muconaldehyde reacted with primary amines to give N-substituted-2(2'-oxoethyl)-pyrroles, which were reduced to N-substituted-2-(2'-hydroxyethyl)-pyrroles by sodium borohydride. The pyrrole-forming reaction is exhibited by valine and its methyl ester, and is being developed with terminal valine in hemoglobin as a means of dose monitoring (Z,Z)-muconaldehyde, a putative metabolite of benzene. Reactions in aqueous solution between (Z,Z)-muconaldehyde and adenosine, deoxyadenosine, guanosine, or deoxyguanosine leading to pyrrole-containing adducts are described. The elucidation of the structures of the adducts was assisted by the study of reactions between (Z,Z)-muconaldehyde and both nucleoside derivatives and a model compound for guanosine. Reactions of (Z,Z)-muconaldehyde are complicated by its isomerization to (E,Z)- and (E-E)-muconaldehyde. The kinetics of this process have been studied in benzene, acetonitrile, and dimethylsulfoxide.